Labour mobility and labour market adjustment in the EU - Alfonso Arpaia; Aron Kiss; Balazs Palvolgyi; Alessandro Turrini (Institute for the Study of Labor (IZA), 2015)
This paper assesses macroeconomic determinants of labour mobility and its role in the adjustment to asymmetric shocks. First, the paper develops stylised facts of mobility at the national and sub-national levels in the EU. Then, it explores the macroeconomic determinants of bilateral migration flows. Econometric evidence suggests that labour mobility increases significantly when a country joins the EU. While euro area membership seems not to be associated with an overall rise in the magnitude of mobility flows, workers do appear more ready to move from countries where unemployment is high to those where it is lower. Thirdly, the paper looks at mobility as a channel of economic adjustment by means of a VAR analysis in the vein of Blanchard and Katz (1992). Results indicate that mobility absorbs about a quarter of an asymmetric shock within 1 year. Movements in response to shocks have almost doubled since the introduction of the euro. Real wages have also become more responsive to asymmetric shocks during the same period.
Keywords: J61; J64; 330; labour mobility; geographic mobility; migration; gravity; adjustment; asymmetric shocks; optimal currency areas; European Union